(untitled) - Norton, Robert L (Dubuque, IA, 1999)
Through its reader-friendly style of writing, clear exposition of complex topics, and emphasis on synthesis and design, the text succeeds in conveying the art of design as well as the use of modern tools needed for analysis of the kinematics and dynamics of machinery. Numerous two-color illustrations are used throughout to provide a visual approach to understanding mechanisms and machines. Analytical synthesis of linkages is covered, and cam design is given a more thorough, practical treatment than found in other texts
Keywords: Machine design,Machinery, Kinematics of,Machinery, Dynamics of,Thiết kế chi tiết máy,Máy móc,Máy móc; Chuyển động học,Động lực học